Usability of self-reported assessment of work functioning in municipal occupational rehabilitation teams: A qualitative study - Momsen, Anne-Mette Hedeager; Tonnesen, Merete; Zwicky-Hauschild, Birgitte; Nielsen, Claus Vinther; Escorpizo, Reuben; Langagergaard, Vivian; Stapelfeldt, Christina Malmose (Frontiers in Rehabilitation Sciences, 2023)
Aims The aims were to explore 1) whether self-reported assessment on work-related functioning, work ability, return-to-work (RTW) self-efficacy and expectation, was useful in the professionals' assessment of sick-listed workers and could guide referral to interventions, and 2) whether self-reporting in addition to "usual practice" could improve the RTW dialogue and involvement in case management. Methods The qualitative study took place in two municipal job centres in 2021. The assessment was based on the Work Rehabilitation Questionnaire, RTW-Self-efficacy Scale-19, single items of self-rated health, work ability and RTW expectations. 36 sSick-listed workers (n=36) were interviewed by telephone. Three focus group interviews were conducted with professionals who had used the questionnaire. Data was coded and analysed thematically. Results Three themes with seven subthemes emerged: 1) accessibility; 2) one tool in the RTW toolbox (subthemes: a supplementary tool, a tool for reflection, facilitating interdisciplinary communication, and enhancing active participation), 3) the value of "ticking boxes" (sub-themes: good days, bad days, the issue of power, and the cultural meaning of words). Conclusions The professionals would not recommend the present questionnaire for use during their rehabilitation team meeting for assessment, interdisciplinary communication or for choice of interventions. However, using the parts assessing RTW (self-efficacy and expectation) combined with a dialogue, may be of value early in the RTW process. The self-reporting assessment tool was perceived to be meaningful to some sick-listed workers, as it provided reflections on important aspects of the RTW process. Some workers believed it may contribute to the rehabilitation team, thereby it could improve their involvement.